Reliability, efficacy and reproducibility of the cervical vertebrae maturation index (CVMI) - Graziela Oro Cericato; Paulo Henrique Luiz de Freitas; Marcos Alan Vieira Bittencourt; Luiz Renato Paranhos (Bioscience Journal, 2014)
Assessing skeletal maturation is an important determinant of successful orthodontic treatment planning for children and adolescents. While several methods are used skeletal maturation assessment, the hand-wrist radiograph is one of the most widely used. However, it does require additional exposing growing patients to additional radiation. Information on skeletal maturation can also be retrieved after evaluation of cervical vertebrae, which are commonly portrayed on the lateral cephalometric radiographs included in standard orthodontic documentation. By means of a systematic review of the available literature, this work aimed to verify the reliability, efficacy, and reproducibility of skeletal age determination based on the evaluation of cervical vertebrae. The LILACS, SciELO and PubMed databases were searched using the keywords "cervical vertebrae" and "cervical maturation". Only texts in Portuguese, Spanish, and English published in the last 10 years were selected. Twenty-nine full articles were retrieved and critically appraised. According to these references, the Cervical Vertebrae Maturation Index appears to be a valid, reliable, and reproducible method for skeletal maturation assessment and may substitute the analysis of hand-wrist radiograph in orthodontic treatment planning.